Adaptive Challenges and Family Support: Patient Self-Management during Treatment for Chronic Hepatitis C. (October 2021) - Bailey, Donald E.; Muir, Andrew J.; Cary, Michael P.; Ammarell, Natalie; Seaver, Sarah; Scirica, Emily; Mah'moud, Mitch; Anderson, Ruth A.
The authors describe a family's adaptive challenges and adaptive work during a family member's treatment for Chronic Hepatitis C. We audiorecorded index and final clinical visits and interviewed participants (patients and providers) following the visits. We interviewed by telephone and reviewed medical records over the course of treatment. Transcripts were analyzed using directed content analysis. Three themes were identified: family adaptive challenges, patient-described aspects of family members' adaptive challenges, and family adaptive work. There were four subthemes related to family adaptive work. The adaptive leadership framework for chronic illness provided direction for future family intervention.